Modeling the scooping phenomenon for the heat transfer in liquid-gas horizontal slug flows - Lange Bassani, Carlos; Pereira, Fernando H.G.; Barbuto, Fausto A.; Morales, Rigoberto E.M. (Applied Thermal Engineering, 2016)
The heat transfer between the deep sea waters and the oil and gas mixtures flowing through production lines is a common situation in the petroleum industry. The optimum prediction of the liquid-gas flow parameters along those lines, when the intermittent flow pattern known as slug flow is dominant, has extreme importance in facilities' design. The mixture temperature drop caused by the colder sea waters, which can be regarded as an infinite medium with constant temperature, directly affects physical properties of the fluids such as the viscosity and specific mass. Gas expansion may also occur due to pressure and temperature gradients, thus changing the flow hydrodynamics. Finally, the temperature gradient affects the thermodynamic equilibrium between the phases, favoring wax deposition and thus increasing pressure drops or even blocking the production line. With those issues in mind, the present work proposes a stationary model to predict the mixture temperature distribution and the two-phase flow heat transfer coefficient based on the mass, momentum and energy conservation equations applied to different unit cell regions. The main contribution of the present work is the modeling of the thermal scooping phenomenon, i.e., the heat transfer between two adjacent unit cells due to the mass flux known as scooping. The model was implemented as a structured Fortran95 code with an upwind difference scheme. The results were compared to experimental data and presented good agreement. The analysis showed that the inclusion of the scooping phenomenon into the model resulted in an averaged 8% improvement in the temperature gradient calculation and heat transfer coefficient prediction for the flowing mixture.
Created from Fastlane, Scopus look-up
Keywords: Heat transfer; Mathematical modeling; Scooping phenomenon; Slug flow